632.IMPLEMENTATION OF A SMART ELEVATOR - Kristina, Jakimovska; Vojdan, Karatrajkov; Anita, Vasileva (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2021)
Elevators are one of the most important mediums of transport in many buildings and working environments. With the development of the architecture, the buildings are getting higher and logically needs to upgrade the way the elevators are currently working or to predict the errors before they happen. The solution lies in changing the current system with a PLC (programmable logic controller). On the other hand, minimization of errors in combination with eco-friendly solutions is the new purpose. This new point of view, which focuses on minimizing and reducing errors, vibrations, more economically is named green elevator. Related to the idea of using green elevators and making buildings more environmentally friendly, the main goal of this paper is to give a new, "green" direction to elevators.